MALAYSIA-REPUBLIC OF KOREA-ASEAN RELATIONS AND THE IMPROVEMENT OF INTER KOREAN RELATIONS - Govindasamy, Geetha (AEI Insights, 2025)
Despite various summits, inter-Korean relations have stalled since 2019. While this is not something new, but the Democratic Republic of Korea’s aggressive expansion of its nuclear and missile programs threatens the regional stability of the Asia Pacific region. Without reviving inter-Korean interaction, there will be no path towards North Korea’s eventual denuclearization process. Though the Association of Southeast Asian nations (ASEAN) is not directly involved in managing the denuclearization issue on the Korean peninsula, the article argues that the Association has a role to play in facilitating inter-Korean ties. As a regional organization, ASEAN has the capability as well as the platform to revive inter-Korean relations. It’s likely that ASEAN is the only regional institution that is trusted by both North and South Korea. Therefore, it can effectively play a role to ease or reduce the trust deficit Pyongyang faces with Seoul. The article examines the strategies that could be employed by ASEAN as well as Malaysia, the ASEAN Chair for the year 2025, in persuading North Korea to revive talks with the South. Nonetheless, it should be noted that ASEAN can only play the role of a facilitator if both the ROK and DPRK accept, and the major powers support it. Keywords: Keywords: regional organization, ASEAN Chair, Inter-Korean Relations, facilitator, multilateralism